EXPANSION OF THE BUSINESS SECTOR - Tilabova Dilafruz Shavkatovna (Web of Journals Publishing, 2025)
This article covers the expansion of the business sector on the basis of issues of development of small and medium-sized businesses in Uzbekistan, as a result of measures aimed at creating economic reforms and a favorable business environment in the country, new opportunities for business activities are being opened.
Keywords: Business, expansion, investment, convenient business environment, small and medium-sized businesses, innovation, technology, export.